18F-FDG PET/CT for initial staging in breast cancer patients: Is there a relevant impact on treatment planning compared to conventional staging modalities? - Krammer, Julia; Schnitzer, Andreas; Kaiser, Clemens G.; Büsing, Karen-Anett; Sperk, Elena; Brade, Joachim; Wasgindt, Sabine; Sütterlin, Marc; Schönberg, Stefan; Wasser, Klaus (European radiology, 2015)
Objective: To evaluate the impact of whole-body 18 F-FDG PET/CT on initial staging of breast cancer in comparison to conventional staging modalities. Methods: This study included 102 breast cancer patients, 101 patients were eligible for evaluation. Preoperative whole-body staging with PET/CT was performed in patients with clinical stage ≥ T2 tumours or positive local lymph nodes (n = 91). Postoperative PET/CT was performed in patients without these criteria but positive sentinel lymph node biopsy (n = 10). All patients underwent PET/CT and a conventional staging algorithm, which included bone scan, chest X-ray and abdominal ultrasound. PET/CT findings were compared to conventional staging and the impact on therapeutic management was evaluated. Results: PET/CT led to an upgrade of the N or M stage in overall 19 patients (19 %) and newly identified manifestation of breast cancer in two patients (2 %). PET/CT findings caused a change in treatment of 11 patients (11 %). This is within the range of recent studies, all applying conventional inclusion criteria based on the initial T and N status. Conclusions: PET/CT has a relevant impact on initial staging and treatment of breast cancer when compared to conventional modalities. Further studies should assess inclusion criteria beyond the conventional T and N status, e.g. tumour grading and receptor status.
Gesehen am 19.02.2018
Im Titel ist "18" hochgestellt